Analysis of Environmental Literacy of Puspita High School Students, Air Kumbang District, Banyuasin Regency - Siti Nurhayati; Wulandari Saputri (Gema Wiralodra, 2024)
This study aims to analyze the environmental literacy of students at Puspita High School, Air Kumbang District, and Banyuasin Regency related to biotic and abiotic components in oil palm plantations. This study uses a quantitative descriptive approach with a data collection method through an environmental literacy questionnaire. The population of this study is 175 students of class X phase E, and the research sample of class X1 is 35 students. The results showed that most of the population had environmental literacy skills at a "High" level, with a frequency of 13 people. The "Medium" and "Very High" categories also have a significant number, 9 and 8 individuals, respectively. The "Very Low" and "Low" categories have the lowest frequencies, with only 2 and 3 individuals, respectively. Overall, this data shows that most individuals in the population have a pretty good level of environmental literacy, with the most significant being in the "High" category. Percentage scores varied from 61.1% to 93.1%. This value shows variations in students' environmental literacy achievement by various aspects or components measured. The highest score is 93.1%, indicating excellent performance in that aspect or component. The lowest score was 61.1%, indicating areas that need further improvement or attention in environmental education. The data provided does not list the average value for all items except for the first item, whose average is 80.74%. It may show a general average of the entire data or just a specific item. Consistency in the maximum score shows that each item has the same maximum score of 72. It indicates that each aspect or component assessed has the same weight or level of difficulty. Overall, the data showed the level of environmental literacy among students, with significant variations in the achievement percentage. Relatively high scores in some aspects suggest that there are areas where learners have a good understanding, while lower scores indicate areas that require further attention in environmental education.